2022
DOI: 10.1101/2022.07.06.498940
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fibromyalgia patients with high levels of anti-satellite glia cell IgG antibodies present with more severe symptoms

Abstract: Objective: Transferring fibromyalgia patient IgG to mice induces pain-like behaviour and fibromyalgia IgG binds mouse and human satellite glia cells (SGCs). These findings suggest that autoantibodies could be part of fibromyalgia pathology. However, it is unknown how frequently fibromyalgia patients have anti-SGC antibodies and how anti-SGC antibodies associate with disease severity. Methods: We quantified serum or plasma anti-SGC IgG levels in two fibromyalgia cohorts from Sweden and Canada using an indirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Caveolar transcytosis represents a mechanism that could potentially be pharmacologically targeted to reduce DRG endothelial permeability, or alternatively co-opted to deliver drugs into the DRG parenchyma (Kiseleva et al, 2018; Marchetti et al, 2019). This could be desirable in sensory ganglionopathies (Amato and Ropper, 2020), which include paraneoplastic and autoimmune conditions, infections, platinum-based chemotherapy (Dzagnidze et al, 2007; Gupta and Bhaskar, 2016), and likely also fibromyalgia (Goebel et al, 2021; Martínez-Lavín, 2021; Krock et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Caveolar transcytosis represents a mechanism that could potentially be pharmacologically targeted to reduce DRG endothelial permeability, or alternatively co-opted to deliver drugs into the DRG parenchyma (Kiseleva et al, 2018; Marchetti et al, 2019). This could be desirable in sensory ganglionopathies (Amato and Ropper, 2020), which include paraneoplastic and autoimmune conditions, infections, platinum-based chemotherapy (Dzagnidze et al, 2007; Gupta and Bhaskar, 2016), and likely also fibromyalgia (Goebel et al, 2021; Martínez-Lavín, 2021; Krock et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Microglial activation has been considered a marker for localized brain neuroimmune mechanisms and a potential key mechanism in central (nociplastic) pain (60). A subset of patients with FM had elevated levels of anti-satellite glial cell antibodies, but this was not associated with cytokine release or with systemic inflammation (61). It has been suggested that the nociplastic pain characteristic of FM, ME/CFS, and long COVID may share similar glial brain activation pathways (62,63).…”
Section: Similar Pathophysiologic Pathways (Table 3)mentioning
confidence: 99%
“…The results demosntrated a correlation between binding of IgG to SGCs and fibromylagia disease severity. These finds show potential for a anti-SGC antibody screening test for FMS to assist personalized treatment options that target autoantibodies [ 30 ].…”
Section: Pathophysiologymentioning
confidence: 99%